Pelatihan Soft Skill dan Hard Skil (Akutansi dan Perpajakan) Pada Siswa di SMK Bina Mandiri Multimedia - Suratminingsih; Taufiq Hidayat; Purwanto; Vera (Sekolah Tinggi Ekonomi Bisnis Syariah Bina Mandiri, 2022)
The current era of digitalization forces and requires millennials to be technology literate in creating and presenting technology-based financial reports while still being based on PSAK applicable in Indonesia. The purpose of this activity is that it is hoped that with a soft kill and hard skill training in compiling financial reports based on digital technology, students will be ready to use them when they enter the world of work, both in making financial reports and reading financial reports. This service activity is carried out at the Bina Mandiri Multimedia Vocational School with the lecture method by providing an overview of both the accounting flow and the basics of financial reports to students, after participating in this activity, result of this activity is that students are able to understand and make the presentation of financial statements as a whole. , along with the aspects inherent in the financial statements, both in terms of taxation and function and can be applied in schools and in everyday life.